Answer:
Explanation:
The given quadratic equation is expressed as
x² - 12x + 36 = 90
Rearranging it in line with the standard form of ax² + bx + c, it becomes
x² - 12x + 36 - 90 = 0
x² - 12x - 54 = 0
The general formula for solving quadratic equations is expressed as
x = [- b ± √(b² - 4ac)]/2a
From the equation given,
a = 1
b = - 12
c = - 54
Therefore,
x = [- 12 ± √(- 12² - 4 × 1 × - 54)]/2 × 1
x = [- 12 ± √(144 - - 216)]/2
x = [- 12 ± √360]/2
x = (- 12 + 18.97)/2 or x = (- 12 - 18.97)/2
x = 3.485 or x = - 15.485